(untitled) (Palíndromo, 2016)
Although still in the process of star- ting my first dissertation seek through this reflection to make some considera- tions about what I’ve been going through and understanding for academic resear- ch. I intend to dwell on the methodologi- cal aspects of research, but also on some other issues that seem present during the process. Finally I make some con- siderations about the work I have been doing and put the research as something open, what happens in your doing and it requires the researcher an intimate rela- tionship with her.